Implementing server-based communication within Ethernet switches - R. Santos (2009)
Real-Time Ethernet (RTE) protocols have difficulties in attaining a bandwidth efficient support of aperiodic message streams in scenarios where strict timeliness requirements have to be met. To overcome such difficulties, the authors proposed recently the Server-SE protocol that deploys server-based traffic scheduling over switched Ethernet using the FTT-SE protocol and COTS switches as platform. This paper extends such work by proposing a new platform, namely the FTT-Enabled Switch recently developed by the authors. The resulting framework provides a high level of determinism, robustness and flexibility, being particularly suited to open systems as servers can easily be added, composed, adapted and removed at run-time. The framework is validated with a prototype implementation. Experimental results show the effectiveness of the framework in guaranteeing a correct temporal behavior even in the presence of traffic with arbitrary arrival patterns and load variations.